2018
DOI: 10.18178/ijlll.2018.4.1.142
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Media for Instructional Purposes

Abstract: The purposes of this study are to find out functions achieved in social media-based activities for instructional purposes, and the faculty members' opinions towards the use of social media for such purposes. Samples include 31 faculty members, Faculty of Humanities and Social Sciences, Suan Sunandha Rajabhat University (SSRU), Bangkok, Thailand. A questionnaire is used to collect data. The study discloses 3 functions achieved in social media-based activities for instructional purposes with average time consump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The extant literature shows notable variations between the personal, professional and instructional use of social media with respect to different regions. For instance, authors in [25] conducted a study to understand the functions of social media usage and opinions of 31 faculty members" towards instructional use of social media. The study revealed positive opinions on delivering content to meet the requirements of their technologically eligible students through interaction.…”
Section: Related Researchmentioning
confidence: 99%
“…The extant literature shows notable variations between the personal, professional and instructional use of social media with respect to different regions. For instance, authors in [25] conducted a study to understand the functions of social media usage and opinions of 31 faculty members" towards instructional use of social media. The study revealed positive opinions on delivering content to meet the requirements of their technologically eligible students through interaction.…”
Section: Related Researchmentioning
confidence: 99%